Adenosine signaling: Optimal target for gastric cancer immunotherapy - Wang, Junqing; Du, Linyong; Chen, Xiangjian (Frontiers in Immunology, 2022)
Gastric cancer (GC) is one of the most common malignancy and leading cause of cancer-related deaths worldwide. Due to asymptomatic or only nonspecific early symptoms, GC patients are usually in the advanced stage at first diagnosis and miss the best opportunity of treatment. Immunotherapies, especially immune checkpoint inhibitors (ICIs), have dramatically changed the landscape of available treatment options for advanced-stage cancer patients. However, with regards to existing ICIs, the clinical benefit of monotherapy for advanced gastric cancer (AGC) is quite limited. Therefore, it is urgent to explore an optimal target for the treatment of GC. In this review, we summarize the expression profiles and prognostic value of 20 common immune checkpoint-related genes in GC from Gene Expression Profiling Interactive Analysis (GEPIA) database, and then find that the adenosinergic pathway plays an indispensable role in the occurrence and development of GC. Moreover, we discuss the pathophysiological function of adenosinergic pathway in cancers. The accumulation of extracellular adenosine inhibits the normal function of immune effector cells and facilitate the effect of immunosuppressive cells to foster GC cells proliferation and migration. Finally, we provide insights into potential clinical application of adenosinergic-targeting therapies for GC patients.